The Policy Reforms through the Incremental Model: Analyses of the Kafala System in Qatar - Ardiyanti, Dwi; Zahrotus, Nilna (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2026)
This research analyzes the incremental model transformation in Qatar’s Kafala system, which has been in the international spotlight since the country was selected to host the 2022 FIFA World Cup. The qualitative method applied in this research is desk research, analyzing data from documents and obtaining related data by summarizing historical economic reforms to create timelines and figures. This study explores transforming the Kafala system into a de-Kafala system due to pressure from international organizations such as the ILO and FIFA. The reforms undertaken included the abolition of exit permits and the implementation of a minimum wage. However, previous research has mostly focused on demonstrating Qatar’s efforts to improve its image on the global scene. However, the results were still incremental and insubstantial, thus unable to address the problem of systemic human rights violations against migrant workers. Despite international attention and support, policy reforms seem aimed more at defusing criticism and maintaining economic stability than at addressing migrant rights issues. This research concludes that the incremental model implemented by the Qatari Government needs to be more effective in addressing humanitarian issues rather than merely meeting international obligations arising from hosting the 2022 FIFA World Cup.